Theoretical perspectives on terminology explaining terms, concepts and specialized knowledge - Faber, Pamela B., 1950-; L'Homme, Marie-Claude (Terminology and lexicography research and practice, 2022)
"The aim of this volume is to provide an overview of different theoretical perspectives on Terminology, from Wüster to other initiatives that have emerged since the beginning of the 1990s. The volume also covers important topics which have significantly influenced Terminology and its evolution. These include variation, multidimensionality, conceptual relations, and equivalence, among others. The twenty-two chapters of the volume, all written by acknowledged experts in the field, explore the questions that different approaches seek to answer. They also describe the theoretical and methodological principles that were devised over the years to characterize, analyze, and represent terminological data. The semi-chronological, semi-thematic organization of chapters not only provides readers with a clear vision of the evolution of ideas in Terminology, but also gives them an understanding as to why some of these ideas were initially challenged. In addition to being accessible to readers unfamiliar with the basic theoretical principles in the field, the chapters provide a showcase of current research in the field, the challenges looming on the horizon, and finally future directions in terminological research. By bringing together work that is often disseminated in different forums and written in different languages, this volume provides a unique opportunity to look at how different theoretical approaches to Terminology offer complementary perspectives on terms, concepts and specialized knowledge, and help to further a better understanding of the complex phenomena that terminologists must successfully deal with in their work"--